2021
DOI: 10.3389/feart.2021.659310
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Subseasonal Forecasting of China Precipitation With a Machine Learning Approach

Abstract: Precipitation change, which is closely related to drought and flood disasters in China, affects billions of people every year, and the demand for subseasonal forecasting of precipitation is even more urgent. Subseasonal forecasting, which is more difficult than weather forecasting, however, has remained as a blank area in meteorological service for a long period of time. To improve the accuracy of subseasonal forecasting of China precipitation, this work introduces the machine learning method proposed by Hwang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…Compared with previous studies, the lagged relationship between climatic phenomena and rainfall in the East China region is addressed in this study. In future research, more climatic variables (Ouyang et al, 2014a; Tang et al, 2021; Wang et al, 2021) can be considered in the rainfall prediction to explore their relative importance in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies, the lagged relationship between climatic phenomena and rainfall in the East China region is addressed in this study. In future research, more climatic variables (Ouyang et al, 2014a; Tang et al, 2021; Wang et al, 2021) can be considered in the rainfall prediction to explore their relative importance in this region.…”
Section: Discussionmentioning
confidence: 99%
“…The sea level pressure (SLP) in the Indian Ocean is relevant to rainfall in the study region [42]. The meridional wind at 850 mb (V-wind) is commonly used as the large-scale atmospheric predictor for rainfall in varying regions [5,[43][44][45]. Correlation coefficient between the large-scale atmospheric variables and rainfall was used to select the spatial grid and the lag month of the large-scale atmospheric variables.…”
Section: Study Area and Datamentioning
confidence: 99%
“…The MultiLLR model of Hwang et al (2019) was also part of a winning solution in the Subseasonal Climate Forecast Rodeo I (Nowak et al, 2020) and has since been used to improve subseasonal precipitation prediction in China (Wang et al, 2021). For each target date, MultiLLR uses a customized backward stepwise procedure to select SubseasonalClimateUSA features relevant for prediction and local linear regression to combine those features into a forecast for each grid point.…”
Section: Multillrmentioning
confidence: 99%
“…Indeed, subseasonal forecasting has long been considered a "predictability desert" due to its complex dependence on both local weather and global climate variables (Vitart et al, 2012). Nevertheless, recent large-scale research efforts have advanced the subseasonal capabilities of operational physics-based models (Vitart et al, 2017;Pegion et al, 2019;Lang et al, 2020), while parallel efforts have demonstrated the value of machine learning and deep learning methods in improving subseasonal forecasting (Li et al, 2016;Cohen et al, 2018;Hwang et al, 2019;Arcomano et al, 2020;He et al, 2020;Yamagami & Matsueda, 2020;Wang et al, 2021;Watson-Parris, 2021;Weyn et al, 2021;Srinivasan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%